O USO DE RECURSOS TECNOLÓGICOS COMO FERRAMENTAS MOTIVACIONAIS NO ENSINO DE LÍNGUA INGLESA PARA ESTUDANTES JOVENS E ADULTOS DA ESCOLA PÚBLICA - de Fátima Pimentel Gomes, Juliana; Ribeiro de Figueiredo, Mônica; da Silva Franco Crespo, Helenita; Ferreira Paixão, Moacir; Menezes Xavier, Elisa; Vieira Fettermann, Joyce (LINKSCIENCEPLACE, 2026)
The aim of this paper is to discuss the use of technological resources as a motivational tool in the English language teaching for young people and adults at public schools. At first, it briefly talks about the English language teaching at public schools. Later, about what the technological resources are and finally, the context of the research is presented. The accomplishment of this paper counts on readings of documents like Os Parâmetros Curriculares Nacionais (1998) and authors like Ausubel, (1980), Margonari (1997), Rodrigues (1997), Gadotti (1999), Oliveira (2000), Nicholls (2001), Paiva (2001), Silveira (2002), Magalhães and Amorim (2003), Oliveira (2012), among others.